2002
DOI: 10.1046/j.1365-2958.2002.03005.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the extracytoplasmic‐function σ Factor σH in Mycobacterium tuberculosis global gene expression

Abstract: SummaryLike other bacterial species, Mycobacterium tuberculosis has multiple sigma (s) factors encoded in its genome. In previously published work, we and others have shown that mutations in some of these transcriptional activators render M. tuberculosis sensitive to various environmental stresses and, in some cases, cause attenuated virulence phenotypes. In this paper, we characterize a M. tuberculosis mutant lacking the ECF s factor s H . This mutant was more sensitive than the wild type to heat shock and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
312
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(339 citation statements)
references
References 25 publications
17
312
1
2
Order By: Relevance
“…4a), which corresponds to the site previously reported (Manganelli et al, 2002;Raman et al, 2001). Activation of this TSP under SDS stress was MprA-dependent (Fig.…”
Section: Interaction Of Mpra With the Sigb Promotersupporting
confidence: 83%
See 3 more Smart Citations
“…4a), which corresponds to the site previously reported (Manganelli et al, 2002;Raman et al, 2001). Activation of this TSP under SDS stress was MprA-dependent (Fig.…”
Section: Interaction Of Mpra With the Sigb Promotersupporting
confidence: 83%
“…SigE is a major stress-responsive sigma factor of M. tuberculosis (Jensen-Cain & Quinn, 2001;Manganelli et al, 1999Manganelli et al, , 2001Raman et al, 2001), and often functions within a regulatory cascade (Manganelli et al, 2002;Raman et al, 2001). SDS exposure upregulates SigE, which then activates 23 genes, including sigB, mprA, mprB and four other transcription factor genes (Manganelli et al, 2001).…”
Section: -9281 G 2007 Sgm Printed In Great Britainmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that this gene is also induced by rifamicin, and that RbpA is able to stimulate the expression of the rRNA operon even in the presence of rifamicin, conferring a basal level of resistance to this drug (Newell et al, 2006). In M. tuberculosis, Rv2050 was shown to be under the transcriptional control of SigH (SigR orthologue) and upregulated after heat shock and disulfide stress (Manganelli et al, 2002). The finding that the expression of this gene is also induced by vancomycin suggests that Rv2050 might contribute to the basal level of drug resistance in mycobacteria as well, opening the possibility to consider it as a novel drug-target candidate.…”
Section: Resultsmentioning
confidence: 99%